Penentuan Aturan Asosiasi Pola Pembelian Pada Minimarket Dengan Algoritma Apriori - Novianti, Agnes; Elisa, Erlin (Forum Kerjasama Pendidikan Tinggi, 2020)
Data mining is a technique for producing information from a data warehouse into new knowledge. Information is very important and useful to achieve a goal, therefore many people who use information, as well as those carried out in sales businesses such as 212 Mart. 212 Mart is located with a residential complex of residents, of course, will affect the level of sales every day, this causes data storage is increasingly growing, besides that the laying of goods is also not following consumer behavior. The association rule analysis with apriori algorithm is the right method to find the association pattern based on consumer shopping patterns so that it can be known the goods purchased at the same time. The results of this study found the highest support and confidence values ​​are Eggs and Noodles, with a support value of 40% and a confidence value of 85.71%.